Qur’an and archeological discoveries: evidence from the Near East - Yaseen, Ghassan Taha (IDOSI, 2011)
This paper examines the archeological remains and historical events that took place in the ancient Near East and compares them with the archaeological facts mentioned in the Holy Qur’an. One of the key features of the Holy Qur’an is that it contains explicit data about groups of people from the past and events in their lives. It gives the reader an idea of these, the significance of their place of residence and stories about the prophets that were sent to them. To help remove doubts about the historical reliability of the Qur’an, this paper has been divided into three parts: The first part deals with the uncovered cities mentioned in the Qur’an. These include the city of Babel (Babylon) in Iraq, “such things as came down at Babylon to the angels Harut and Marut” (Surah Al Baqarah 2: 102), the city of Iram (Ubar) in Yemen “Have you not seen how your Lord dealt with ‘Ad? The residents of Iram, the city of lofty pillars, the like of which had never been built in other cities” (Surah Al Fajr 89: 6-8), the city of Saba in Yemen, “For the people of Saba (Sheba, presently a town in Yemen) there was indeed a sign in their dwelling place: two gardens - one to the right and one to the left.” (Saba 34: 15) and various other cities mentioned in the Ebla Tablets such as the city of Sodom and Gomorrah where the people of Lot lived. The second part deals with prophets mentioned in the Quran such as Noah, Abraham, Ishmael and Moses. Noah identified in the Akkadian Tablets under the name of Ut-napishtim, which is considered to be the Babylonian Noah and it is mentioned in the tablet number eleven of the Epic of Gilgamesh (the flood story) and discovered among the many tablets from the Ashurbanipal’s library in the Nineveh and kept know in British Museum in London. Other prophets’ names appeared in the Ebla Tablets such as Abraham and Ishmael. Moses’ name appeared in the Egyptian Hieroglyph Inscription. The third part compares the many stories revealed in the Qur’an with that of Archaeological discoveries. These include, Moses’ Pharaoh’s and mummification “This day shall we save in thee in the body, that thou mayest be a sign to those who come after thee!” (Yunus 10: 92), the story of Sargon of Akkad and Moses that shows much similarity to the tablet discovered from the New Assyrian period around 911-612 BC, the story of Queen Saba and Solomon in the beginning of the first Millennium BC and the story of the people of the Kahf (the cave of the seven sleepers), uncovered near Amman in Jordan in 1963 CE, or in Yemen and Turkey. As can be seen, the information provided by the Qur’an about events of the past is in total agreement with historical information; this is another evidence of the fact that the Qur’an is the Word of Allah.